Posttraumatic Growth and Its Measurement: A Closer Look at the PTGI’s Psychometric Properties and Structure - Jozefiaková, Bibiána; Kaščáková, Natália; Adamkovič﻿﻿﻿, Matúš; Hašto, Jozef; Tavel, Peter (Frontiers in Psychology, 2022)
Despite its negative connotation, surviving trauma can result in improvements in some of the domains of one’s life. This phenomenon is known as posttraumatic growth and is usually measured using the Posttraumatic Growth Inventory (PTGI). Given the ambiguous results of the existing validation studies, the present study aimed to verify the psychometric properties of the Slovak version of the (PTGI) in a representative sample of Slovak citizens. Although the results suggest that a modified one-factor structure fitted the data best, other issues such as extremely high correlations between the latent factors, related to the PTGI’s factor structure were observed. It is likely that the application of the latent variable model does not represent the essence of PTG adequately and the network approach thus appears to be a far more suitable conceptualization of PTG. More detailed information on between-person differences and within-person changes in PTG could help to tailor more effective interventions or preventative programs.